2013
DOI: 10.1016/j.ijid.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

High vancomycin minimum inhibitory concentration and clinical outcomes in adults with methicillin-resistant Staphylococcus aureus infections: a meta-analysis

Abstract: SUMMARY Background Patients with methicillin-resistant Staphylococcus aureus (MRSA) infections caused by isolates with a high but ‘susceptible’ minimum inhibitory concentration (MIC) to vancomycin may suffer poor outcomes. The aim of this study was to determine the association of high compared to low vancomycin MICs and clinical outcomes (treatment failure and mortality) in patients with MRSA infections. Methods PubMed, the Cochrane Library, and electronic abstracts from meetings were queried from January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 43 publications
3
69
0
1
Order By: Relevance
“…24) Host factors, pathogen factors, clinical management, and microbiological factors, such as methicillin resistance and VCM MICs, were found to be associated with mortality. [5][6][7]9,24) However, a recent meta-analysis reported no differences in the risk of death in patients with S. aureus high and low VCM MICs. 8) Our previous study showed that there was no significant difference between the survival and dead group in the VCM AUC/MIC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24) Host factors, pathogen factors, clinical management, and microbiological factors, such as methicillin resistance and VCM MICs, were found to be associated with mortality. [5][6][7]9,24) However, a recent meta-analysis reported no differences in the risk of death in patients with S. aureus high and low VCM MICs. 8) Our previous study showed that there was no significant difference between the survival and dead group in the VCM AUC/MIC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses have attempted to address the association between MIC and clinical outcomes. [5][6][7] In contrast to these studies, a recent meta-analysis examining 8291 episodes reported no differences in the risk of death between patients with S. aureus high and low VCM MICs. 8) These results highlight the current lack of consensus regarding the relationship between VCM MICs and the prognosis of patients with MRSA infections.…”
mentioning
confidence: 98%
“…However, these were written in 2010 and evidence has continued to emerge since their inception and subsequent publication. Meta-analyses have consistently shown poorer outcomes with MICs approaching the breakpoint (>1 mg/L), including mainly episodes of bacteraemia but also pneumonia and skin and soft-tissue infections (SSTIs) [12][13][14]. The vancomycin MIC was significantly associated with mortality for MRSA infection irrespective of the source of infection or MIC methodology [odds ratio (OR) = 1.64, 95% confidence interval 1.14-2.37], although this was mostly attributable to bloodstream infections and Etest MICs of 2 mg/L [12].…”
Section: The Vancomycin Breakpointmentioning
confidence: 99%
“…19 A meta-analysis published in 2014 comparing the clinical course of patients with MRSA bacteremia failed to demonstrate an association between a MIC of vancomycin below or above 1.5 µg/L and mortality. 20 In this study, the analysis was not adjusted for severity or delay in definite therapy; however, it is worth noting that all deceased patients were in the MRSA group.…”
Section: Discussionmentioning
confidence: 99%